Antigone between love and fury (or Griselda Gambaro before old Sophocles) - Reisz, Susana (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
Antigone between love and fury (or Griselda Gambaro before old Sophocles)
Keywords: Sophocles; Antigone; Griselda Gambaro